Kerja Sama Orang Tua dan Guru dalam Meningkatkan Hasil Belajar Siswa di SD BPD Podimor Padange Kecamatan Morotai Jaya Kabupaten Pulau Morotai - Jufri Bona; Subhan Hayun; Amrin Sibua (Peneliti.net, 2021)
and parents in increasing motivation and learning outcomes of elementary school students (SD) BPD Podimor Padange. 2). Barriers to cooperation between teachers and parents to increase motivation and learning outcomes of Elementary School (SD) BPD Podimor Padange students. 3). efforts to collaborate with parents in increasing motivation and learning outcomes of elementary school students (SD) BPD Podimor Padange. This type of research used in this research is qualitative research. The results in this study are, 1). The form of collaboration between teachers and parents in improving student learning outcomes is communication, recitation, parental involvement in children's learning at home. 2). The obstacles experienced by the madrasah in establishing cooperation between teachers and parents to improve student learning outcomes are influenced by internal and external factors. Internal factors, namely the teacher's view of parents and teacher constraints. While external factors are the views of parents, life demands and attitudes of parents. 3) Efforts made by SD BPD Podimor Padange in realizing cooperation between teachers and parents in improving student learning outcomes are: a). Schools provide the best service to parents of students. b) Schools equate perceptions and values ​​instilled by the school with the values ​​taught by parents by conducting initial communication. c) Provide opportunities for parents to be involved in learning at home